Finland’s Election: Ideology, Power, and Critique behind the Loss of Sanna Marin in The Guardian - Murdhi Fida Alfaaz; Angelica Monalisa; Agis Andriani (Siliwangi University, 2023)
Finland’s prime minister election result is out, impacting a huge shock in European politics. This study examines The Guardian's coverage of the Finnish Prime Minister Sanna Marin's loss in the recent election, utilizing Ruth Wodak's approach to Critical Discourse Analysis. The study aims to uncover underlying ideologies, power relations, and potential critiques in The Guardian's coverage. The article analyzes The Guardian's April 4th, 2023, publication titled